2018
DOI: 10.1002/hyp.13269
|View full text |Cite
|
Sign up to set email alerts
|

Using source‐specific models to test the impact of sediment source classification on sediment fingerprinting

Abstract: Sediment fingerprinting estimates sediment source contributions directly from river sediment. Despite being fundamental to the interpretation of sediment fingerprinting results, the classification of sediment sources and its impact on the accuracy of source apportionment remain underinvestigated. This study assessed the impact of source classification on sediment fingerprinting based on diffuse reflectance infrared Fourier transform spectrometry (DRIFTS), using individual, source-specific partial leastsquares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
(127 reference statements)
0
11
0
Order By: Relevance
“…Estimated contributions from riverbanks are therefore highly uncertain, as additional (unclassified) sources might still be captured within this group. However, the analysis also suggests that the part represented by the riverbank samples is an important source; omitting the riverbank as a source impacts significantly on the estimated contributions of other sources (Vercruysse and Grabowski, ). Therefore, riverbank was retained as a potential source, but the high confidence intervals should be kept in consideration.…”
Section: Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…Estimated contributions from riverbanks are therefore highly uncertain, as additional (unclassified) sources might still be captured within this group. However, the analysis also suggests that the part represented by the riverbank samples is an important source; omitting the riverbank as a source impacts significantly on the estimated contributions of other sources (Vercruysse and Grabowski, ). Therefore, riverbank was retained as a potential source, but the high confidence intervals should be kept in consideration.…”
Section: Methodsmentioning
confidence: 98%
“…The discriminant analysis demonstrated that urban street dust and material from grassland topsoil in the three lithological areas can be discriminated well based on their DRIFTS spectra, while riverbank has a lower degree of discriminatory power (Vercruysse and Grabowski, ). The difference in discriminatory power can be attributed to the primary origin of the sources.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations